Effect of private versus emergency medical systems transportation in motor vehicle accident victims: Trauma Center Experience in Saudi Arabia - Mohammed S Alshahrani (Wolters Kluwer Medknow Publications, 2017)
Objective: To assess the effect of the mode of transportation of trauma patients (emergency medical service [EMS] vs. non-EMS) on their final clinical outcome in terms of mortality and length of hospital stay. Materials And Methods: A retrospective study included all patients who were involved in motor vehicle crashes, and who were transferred immediately to an emergency department of a trauma care center from December 2008 to December 2012. Patients were classified into two groups: those brought through EMS and those brought by non-EMS (private transport). Information on demographic characteristics including age and gender was recorded and medical data such as blood pressure, pulse, oxygen saturation, temperature, initial Glasgow Coma Score (GCS), saturation, temperature, initial Glasgow Coma Score (GCS), injury severity score (ISS), and final outcome (discharged or expired) were obtained. Descriptive statistics, mean and standard deviation (SD) were computed for continuous variables and statistical significance was tested by t-test or Mann-Whitney U-test. Categorical variables were described by frequency distribution and percentages; Chi-square or Fisher's exact test as appropriate were employed to test for statistical significance. Logistics regression was performed with mortality as dependent variable and mode of transport and all demographic and prehospital variables as independent variables. A general linear model analysis was performed to test whether the mode of transport was significant to length of hospital stay in EMS and non-EMS clients. Results: Out of 308 patients identified during the study period, 232 were transported through EMS and 76 through non-EMS. The two groups were similar with regard to mortality and length of stay. The crude mortality rate was 30.6% (95% confidence interval [CI]: 24.64-36.53) in the EMS group and 28.9% (95% CI: 18.44-38.76) in the non-EMS group (p = 0.785). The average length of hospital stay was 9 days (interquartile range [IQR] = 8, 95% CI: 7.3-10.1) for the EMS group and 8 days (IQR = 9.5, 95% CI: 6.7-10.9) for the non-EMS group (p = 0.803). Multivariate analysis showed that of the study variables, only the injury severity score (ISS) and Glasgow coma score (GCS) were significant to mortality (p < 0.01), and GCS was more significant to the length of hospital stay (p < 0.01). Conclusions: There was no significant difference between the EMS and non-EMS groups as they relate to mortality and length of stay in hospital. However, the mortality and length of hospital stay was statistically significant to ISS and GCS.